Laws and Ordinances Governing the City of Chicago 88-89 (Murray F. Tuley ed., 1873) - (:unkn) unknown (My University, 1866)
Chapter 31-Parks and Public Grounds, § 6-Firearms and Missiles Prohibited-Protection of Shrubbery. Revised Ordinance of 1866: Prohibited carry of firearms, throwing stones or other missiles with any of the public parks of Chicago. Forbade cutting, breaking, or in any way injuring or defacing trees, shrubs, plants, turf, or any buildings, fances, bridges, or other construction or property.
Keywords: CARRY - CERTAIN PUBLIC PLACES